Leadership, Policy Making, and Economic Growth in African Countries : The Case of Nigeria - Iyoha, Milton A. (World Bank, Washington, DC, 2017)
Nigeria's long-run growth performance has been extremely poor. Between 1960 and 2000, real income per capita grew at only 0.43 percent per year. The situation improved between 2001 and 2006 when real per capita Gross Domestic Product (GDP) grew at an average annual rate of 4.2 percent. This paper demonstrates that the superior growth performance during 2001-06 is largely attributable to the impact of better leadership and economic policy making. The improved performance of the economy after 2003 arose from implementing a comprehensive economic reform program focusing on four main areas: macroeconomic reform; structural reform; governance and institutional reform; and public sector reform. The reforms, backstopped by improved oil revenue management, monetary policy implementation, and debt management, improved overall macroeconomic policy making. This resulted in real GDP growth averaging 7.1 percent per year between 2003 and 2006, an inflation rate of 10 percent in 2006, foreign exchange reserves of US$45 billion in 2006, and total external debt of only US$5 billion in 2006. Clearly, between 1960 and 2000, Nigeria's policy choices were poor, and the reforms that sought to correct them were plagued by inconsistencies, policy reversals, and lack of coherence. In contrast, due to good leadership, the reforms adopted in 2003 were consistent and have been implemented in a coherent manner.